2007
DOI: 10.1152/ajprenal.00184.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inhibition of nuclear factor-κB attenuates renal injury in the 5/6 renal ablation model

Abstract: Fujihara CK, Antunes GR, Mattar AL, Malheiros DMAC, Vieira JM Jr, Zatz R. Chronic inhibition of nuclear factor-B attenuates renal injury in the 5/6 renal ablation model. Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 40 publications
8
98
0
11
Order By: Relevance
“…The increasing awareness of NF-B diversity in terms of regulatory components and actions calls for more detailed preclinical studies to pinpoint the timeframe and optimal target for potential clinical therapy. 79 Decreased proteinuria Diabetic nephropathy 80 Decreased inflammation AKI, sepsis 39 Decreased inflammation AKI; zymosan 81 Decreased inflammation 5/6 renal ablation model 82 Decreased inflammation AngII-infused renal injury 54,83 Decreased inflammation Parthenolide Glomerulonephritis 56 Decreased inflammation, proteinuria AKI; cisplatin 87 Decreased inflammation, proteinuria AngII-induced kidney injury 67 Decreased inflammation gliotoxin Glomerulonephritis 56 Decreased inflammation, proteinuria DHMEQ Glomerulonephritis 88 Decreased inflammation, proteinuria Specific approaches decoy B ODN Glomerulonephritis, crescentic 90 Decreased inflammation Allogenic renal transplant 92 Decreased inflammation AKI, ischemia-reperfusion 89 Decreased inflammation UUO 91 Decreased inflammation p50 siRNA AKI, sepsis 39 Improved renal function, decreased inflammation p50 knockout AKI, endotoxemia 40 Prolonged inflammation, increased mortality IB␣ super-repressor Protein overload proteinuria 93 Decreased inflammation DHMEQ, dehydroxymethyl-epoxyquinomicin; ODN, oligodeoxynucleotides; PDTC, pyrrolidinedithiocarbamate; siRNA, small interfering RNA; UUO, unilateral ureteral obstruction.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing awareness of NF-B diversity in terms of regulatory components and actions calls for more detailed preclinical studies to pinpoint the timeframe and optimal target for potential clinical therapy. 79 Decreased proteinuria Diabetic nephropathy 80 Decreased inflammation AKI, sepsis 39 Decreased inflammation AKI; zymosan 81 Decreased inflammation 5/6 renal ablation model 82 Decreased inflammation AngII-infused renal injury 54,83 Decreased inflammation Parthenolide Glomerulonephritis 56 Decreased inflammation, proteinuria AKI; cisplatin 87 Decreased inflammation, proteinuria AngII-induced kidney injury 67 Decreased inflammation gliotoxin Glomerulonephritis 56 Decreased inflammation, proteinuria DHMEQ Glomerulonephritis 88 Decreased inflammation, proteinuria Specific approaches decoy B ODN Glomerulonephritis, crescentic 90 Decreased inflammation Allogenic renal transplant 92 Decreased inflammation AKI, ischemia-reperfusion 89 Decreased inflammation UUO 91 Decreased inflammation p50 siRNA AKI, sepsis 39 Improved renal function, decreased inflammation p50 knockout AKI, endotoxemia 40 Prolonged inflammation, increased mortality IB␣ super-repressor Protein overload proteinuria 93 Decreased inflammation DHMEQ, dehydroxymethyl-epoxyquinomicin; ODN, oligodeoxynucleotides; PDTC, pyrrolidinedithiocarbamate; siRNA, small interfering RNA; UUO, unilateral ureteral obstruction.…”
Section: Resultsmentioning
confidence: 99%
“…15 Inhibition of renal inflammation by different maneuvers is therapeutically effective, resulting in an amelioration of renal fibrotic lesions in various experimental animal models. 16,17 Several lines of evidence have suggested a potential antiinflammatory activity of vitamin D in CKD. 6,18 In animal models of primary glomerular diseases, administration of vitamin D reduces glomerular infiltration of inflammatory cells.…”
mentioning
confidence: 99%
“…PDTC had been used in a previous study of adult rats, and found to be effective by the oral route. 12 In preliminary experiments with lactating rats, PDTC was also shown to be effective by this route, and the dose of 280 mg kg -1 day -1 was found to be the highest dose not causing death or severe growth retardation of dams or pups. After weaning, male rats were kept in cages in groups of no more than four, receiving ad libitum food and water.…”
Section: Experimental Groupsmentioning
confidence: 97%
“…[8][9][10][11] Accordingly, continuous inhibition of this system exerts a protective effect in an experimental model of chronic kidney disease. 12 However, it is presently unknown whether the NF-kB system participates in organogenesis and, particularly, whether blockade of this system during nephrogenesis would lead to changes similar to those observed with administration of RAS suppressors.…”
Section: Introductionmentioning
confidence: 99%